ANALISIS KEJADIAN GASTRITIS PADA SISWA SMK IBRAHIMY 1 P2S2 SUKOREJO DI KLINIK PRATAMA IDAMAN AS’ADIAH SUKOREJO SITUBONDO - Gasim Soka, Burhanudin; Kholdah, Nur Diana (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
Gastritis is an inflammatory condition of the gastric mucosa which can be acute and chronic due to the patient's lack of attention to health, one of which is the adoption of an unhealthy lifestyle. People who often consume foods that can stimulate stomach acid production and have irregular eating patterns can usually get gastritis. One way to prevent gastritis is to get used to eating regularly, chew food well, don't eat too much, don't lie down after eating, eat less spicy and sour foods, eat less foods that cause gas, don't eat foods that are too cold and hot , reduce fried foods, reduce consumption of chocolate. In addition, reduce stress and avoid foods that trigger gastritis. The research conducted was a non-experimental descriptive study with cross-sectional data collection. The purpose of this study was to determine the description of gastritis therapy, the incidence of gastritis and the factors that cause gastritis. The results showed that the most widely used therapy was ranitidine + gastrucid 20%, the incidence rate was 15%, the biggest factor causing gastritis was often eating spicy food 81.7%.